1996
DOI: 10.1021/jp961225s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Metal on the Organization of Tetraamidometallophthalocyanines in Langmuir−Blodgett Films

Abstract: Metallophthalocyanines (MPc's) [M being one of the following metal ions:  Co(II), Ni(II), Cu(II), or Zn(II)], bearing amide side chains and being highly soluble in organic solvents, have been synthesized by starting from the corresponding phthalonitrile. All four compounds can form Langmuir and Langmuir−Blodgett films, but interestingly, their behavior as monolayers was shown to be very much dependent on the central metal ion. The study of Π−A isotherms, low-angle X-ray diffraction patterns, and IR dichroïsm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…This result is probably due to the hydrophilicity of metallomacrocycle, i.e. the difference in coordination of water molecule to central metal [9]. On the other hand, both molecules showed similar π-A curves above the surface pressure of 20 mN/m.…”
Section: IIImentioning
confidence: 94%
See 1 more Smart Citation
“…This result is probably due to the hydrophilicity of metallomacrocycle, i.e. the difference in coordination of water molecule to central metal [9]. On the other hand, both molecules showed similar π-A curves above the surface pressure of 20 mN/m.…”
Section: IIImentioning
confidence: 94%
“…In addition, central metals of phthalocyanines also influence the orientation because of difference in metallomacrocycle-water interactions, i.e. the hydrophilicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fully compressed films show the Pc rings tilted by 50-60º. Fouriaux et al [20] studied the influence of the metal, including Zn, on LB films of tetraamidometalloPc, and they concluded that Co and Zn Pc are coordinated with water and therefore oriented with an angle of 60º with respect to the normal to the air-water interface or to the substrate; NiPc is not coordinated with water, while π-π interactions become possible and the molecules can orient more vertically; and CuPc is an intermediate case. Cook et al [21] reported the presence of domains in LB multilayers of octan-alkoxy Pc in which the molecules are arranged with their planes approximately perpendicular 6 to the substrate surface.…”
Section: Introductionmentioning
confidence: 97%
“…The LB technique for the assembly of ZnPc has been used in a limited number of works [1,9,[19][20][21][22][23], and recently Qiu et al [24] used the horizontal transfer technique (Langmuir-Schaefer, LS).…”
Section: Introductionmentioning
confidence: 99%
“…These applications usually require a thin film deposited on a solid substrate. Several studies have investigated these systems and their particular structure, and some of them have studied the characteristics of organized Langmuir and Langmuir-Blodgett (LB) films [1,20,[30][31][32][33][34][35]. Studies in LB films of MPc are important in understanding of interfacial spectroscopic processes occurring in organic materials deposited on inorganic solid substrates, for further developing of photovoltaics and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%